2009
DOI: 10.1017/s0954579409000285
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depressive symptoms in infancy: Unique contribution to children's depressive symptoms in childhood and adolescence?

Abstract: This prospective 20-year study assessed associations between maternal depressive symptoms in infancy, childhood, and adolescence and child and adolescent depressive symptoms in a sample of families at high psychosocial risk. Maternal symptomatology was assessed with the Center for Epidemiological Studies-Depression Scale (CES-D;Radloff, 1977) when children were infants (12 months), school-aged (age 8), and adolescents (age 19). Children's depressive symptoms were measured at age 8 (Dimensions of Depression Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
3
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 78 publications
4
102
3
9
Order By: Relevance
“…De acordo com a Tabela 3, pode-se observar que todos os 11 estudos avaliaram a fase escolar e incluíram, além desta, a fase pré-escolar ou a adolescência, com destaque para três artigos 16,33,34 que abrangeram desde a pré-escola até a adolescência. As variáveis abordadas para as crianças foram psicopatologia e problemas de comportamento, sendo que três estudos 26,33,34 analisaram tanto comportamentos internalizantes quanto externalizantes.…”
Section: Fase Dounclassified
See 1 more Smart Citation
“…De acordo com a Tabela 3, pode-se observar que todos os 11 estudos avaliaram a fase escolar e incluíram, além desta, a fase pré-escolar ou a adolescência, com destaque para três artigos 16,33,34 que abrangeram desde a pré-escola até a adolescência. As variáveis abordadas para as crianças foram psicopatologia e problemas de comportamento, sendo que três estudos 26,33,34 analisaram tanto comportamentos internalizantes quanto externalizantes.…”
Section: Fase Dounclassified
“…Na adolescência, os estudos relataram predomínio de difi culdades para as meninas, com três artigos que identifi caram problemas internalizantes 20,33 e sintomas depressivos 27 , além de um estudo 34 que relatou maior impacto da depressão materna para as meninas do que para os meninos. Quanto aos meninos, apenas um estudo 16 identifi cou a presença de sintomas depressivos nessa faixa etária.…”
Section: Fase Dounclassified
“…The latest research supports the theory that this early interaction between the parents and the infant has a long term influence on the child even in terms of a biological nature [6]. A traumatic experience that occurs during this bonding and connecting process between the parents and the infant can manifest itself in potential dysfunction or with problems of a psychological or emotional nature [6].…”
Section: Introductionmentioning
confidence: 74%
“…A traumatic experience that occurs during this bonding and connecting process between the parents and the infant can manifest itself in potential dysfunction or with problems of a psychological or emotional nature [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that the association between maternal depression and offspring is stronger in daughters than sons [70,74,75]. However, other studies have not reported gender differences [62,80]. The etiology of depressed child can range according children's development stage too [62].…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%